A case of typhoidal tularemia in a male Japanese farmer - Kiwamu Nakamura; Hiromi Fujita; Tomoya Miura; Yu Igata; Masashi Narita; Naota Monma; Yasuka Hara; Kyoichi Saito; Akinori Matsumoto; Keiji Kanemitsu (International Journal of Infectious Diseases, 2018)
In Japan, most tularemia cases occur after contact with hares (hunting, cooking) and involve the glandular or ulceroglandular form. Here, we present a case of typhoidal tularemia in a 72-year-old Japanese male farmer who presented with fever, fatigue, and right lower abdominal pain. Computed tomography revealed intestinal wall thickening at the ascending colon, pleural effusion, and ascites. Following an initial diagnosis of bacterial enteric infection, his symptoms deteriorated after a week-long cephalosporin treatment course. The patient lived in an area endemic for scrub typhus; the antibiotic was changed to a tetracycline on suspicion of scrub typhus infection. His symptoms rapidly improved after initiation of minocycline treatment. Later, blood tests revealed marked increases in serological tests against Francisella tularensis exclusively, and the patient was diagnosed with typhoidal tularemia. Typhoidal tularemia may be characterized by any combination of general symptoms, but does not exhibit the local manifestations associated with other forms of tularemia. The patient, in this case, had no direct contact with hares or other wild animals and did not present with local manifestations of tularemia. Physicians should consider this disease, especially when tick-borne disease is suspected in the absence of local wounds, eschar, ulcers, or lymphadenopathy.